Responsiveness assessment of a 3D tetra-culture alveolar model exposed to diesel exhaust particulate matter. (December 2018) - Fizeșan, Ionel; Chary, Aline; Cambier, Sébastien; Moschini, Elisa; Serchi, Tommaso; Nelissen, Inge; Kiss, Béla; Pop, Anca; Loghin, Felicia; Gutleb, Arno C.
Abstract: The aim of the current study was to evaluate the responses of a 3D tetra-culture alveolar model cultivated at the air-liquid-interface (ALI) after apical exposure to diesel exhaust particulate matter (DEPM) based on the three-tiered oxidative stress concept. The alveolar model exposed to increasing doses of DEPM (1.75–5 μg/cm 2 ) responded with increasing activity of the anti-oxidant defense mechanisms (Nrf2 translocation, increased gene expression for anti-oxidant proteins and increased HMOX-1 synthesis) (tier 1). Higher exposure generated a proinflammatory response (NF-kB translocation, increased gene expression of pro-inflammatory cytokines and adhesion molecules, and increased IL-6 and IL-8 synthesis) (tier 2) and, finally, the highest doses applied resulted in a decrease of cell viability due to necrosis (extra-cellular release of LDH) or apoptosis (increased expression of the pro-apoptotic genes CASP7 and FAS) (tier 3). Overall, the results of our study demonstrate that the 3D tetra-culture model when directly exposed to DEPM potently generates a realistic response according to the three-tiered oxidative stress concept. Further evaluation and benchmarking against currently used in vivo rodent models is needed to show its suitability, and to serve in the future as an alternative for in vivo studies in the hazard evaluation of inhalable irritants. Highlights: Exposure of the 3D tetra-culture model to diesel exhaust particulate matter (DEPM) was performed at the air-liquid-interface. DEPM exposure induced anti-oxidant defense mechanisms, pro-inflammatory responses and affected the cellular viability. The 3D tetra-culture model may serve in the future as an in vitro alternative.